Contact irritant responses of Aedes aegypti Using sublethal concentration and focal application of pyrethroid chemicals. - Hortance Manda; Pankhil Shah; Suppaluck Polsomboon; Theeraphap Chareonviriyaphap; Fanny Castro-Llanos; Amy Morrison; Roxanne G Burrus; John P Grieco; Nicole L Achee (Public Library of Science (PLoS), 2013)
BACKGROUND: Previous studies have demonstrated contact irritant and spatial repellent behaviors in Aedes aegypti following exposure to sublethal concentrations of chemicals. These sublethal actions are currently being evaluated in the development of a push-pull strategy for Ae. aegypti control. This study reports on mosquito escape responses after exposure to candidate chemicals for a contact irritant focused push-pull strategy using varying concentrations and focal application. METHODS: Contact irritancy (escape) behavior, knockdown and 24 hour mortality rates were quantified in populations of female Ae. aegypti under laboratory conditions and validated in the field (Thailand and Peru) using experimental huts. Evaluations were conducted using varying concentrations and treatment surface area coverage (SAC) of three pyrethroid insecticides: alphacypermethrin, lambacyhalothrin and deltamethrin. RESULTS: Under laboratory conditions, exposure of Ae. aegypti to alphacypermethrin using the standard field application rate (FAR) resulted in escape responses at 25% and 50% SAC that were comparable with escape responses at 100% SAC. Significant escape responses were also observed at <100% SAC using ½FAR of all test compounds. In most trials, KD and 24 hour mortality rates were higher in mosquitoes that did not escape than in those that escaped. In Thailand, field validation studies indicated an early time of exit (by four hours) and 40% increase in escape using ½FAR of alphacypermethrin at 75% SAC compared to a matched chemical-free control. In Peru, however, the maximum increase in Ae. aegypti escape from alphacypermethrin-treated huts was 11%. CONCLUSIONS/SIGNIFICANCE: Results presented here suggest a potential role for sublethal and focal application of contact irritant chemicals in an Ae. aegypti push-pull strategy to reduce human-vector contact inside treated homes. However, the impact of an increase in escape response on dengue virus transmission is currently unknown and will depend on rate of biting on human hosts prior to house exiting.